A sensitive HPLC-FLD method for the quantitative determination of 3-chloro-1, 2-propanediol by pre-column fluorescence derivatization with 9-(2-Hydroxypropyl)adenine. Issue 9 (15th June 2021) - Du, Yan; Hu, Jinhua; Hu, Zhixiong; Zhang, Weinong; Qi, Yutang; Zhang, Yanpeng; Li, Xiaomin; Liu, Yi
Abstract: In this paper, a sensitive method for the determination of 3-chloro-1, 2-propanediol (3-MCPD) by high performance liquid chromatography-fluorescence detection (HPLC-FLD) was established, in which 9-(2-Hydroxypropyl) adenine (HP-Ade) was selected as the fluorescent derivatization reagent because of its good water solubility and hydrophobicity. The principle of the method lies in the origination of chloroacetaldehyde with the periodate oxidation of 3-MCPD and its' fluorescence derivatization by HP-Ade to produce a strong fluorescent substance, name as 1- N 6 -vinylidene-9-(2-hydroxypropyl)adenine (ε-HP-Ade), used for quantitative determination of 3-MCPD by HPLC-FLD. Some mobile phase conditions and incubation parameters related with the method features were studied and optimized. Under the optimal conditions, the method shows high sensitivity, good linearity ( r 2 = 0.999) and good repeatability (RSD% between 1.04% and 2.55%), the detection limit (LOD) and quantification limit (LOQ) were 0.02 ng/mL and 0.06 ng/mL respectively. It has been successfully applied for the determination of various edible vegetable oil samples, the chromatogram shows symmetrical peak shape, perfect separation and very "clean" profiles. In comparison with gas chromatography-mass spectrum (GC-MS), the pretreatment process of the proposed method was totally operated in aqueous phase, the instrument requirements and cost are relatively lower, thus it will provide another choice for the routine analysis of 3-MCPD. Graphical Abstract: UF0001